Immune Tolerance vs. Immune Resistance: The Interaction Between Host and Pathogens in Infectious Diseases - Ahmad, Hafiz Ishfaq; Jabbar, Abdul; Mushtaq, Nadia; Javed, Zainab; Hayyat, Muhammad Umar; Bashir, Javaria; Naseeb, Iqra; Abideen, Zain Ul; Ahmad, Nisar; Chen, Jinping (Frontiers in Veterinary Science, 2022)
The immune system most likely developed to reduce infections' harmful impact on the host's homeostasis. This defense approach is based on the coordinated activity of innate and adaptive immune system components, which detect and target infections for containment, killing, or expulsion by the body's defense mechanisms. These immunological processes are responsible for decreasing the pathogen burden of an infected host to maintain homeostasis that is considered to be infection resistance. A second, and probably more essential, defense mechanism is associated with immune-driven resistance to infection: it helps to reduce the level of dysfunction imposed on host parenchymal tissues during infection without having a direct detrimental effect on pathogens. This defense strategy, known as disease tolerance, is based on tissue damage control mechanisms that prevent pathogens from causing harmful effects on the body. It also uncouples immune-driven resistance mechanisms from immunopathology and disease, allowing the body to fight infection more effectively. In this review, we discuss the cellular and molecular processes that build disease tolerance to infection and the implications of innate immunity on those systems. In addition, we discuss how symbiotic relationships with microbes and their control by particular components of innate and adaptive immunity alter disease tolerance to infection.